The Concept of General Balance and Efficiency in Sharia Economics - Sarmadani Sarmadani; Muslimin Kara; Rahmawati Muin (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
The concept of general balance and efficiency is an important element in the economic system because it is related to the optimization of resource allocation and the creation of community welfare. However, conventional economic approaches that are oriented towards market efficiency and profit maximization are considered not fully able to realize distributive justice, thus giving rise to various problems such as income inequality, speculation, and economic instability. This research aims to analyze the concept of general balance and efficiency in the perspective of sharia economics and explain its implementation in building a fair and sustainable economic system. The research uses a qualitative approach with the library research method. Data was obtained from various secondary sources in the form of scientific journals, books, regulations, and documents relevant to sharia economics, then analyzed using content analysis techniques. The results of the study show that the concept of general equilibrium in the Islamic economy is not only oriented towards the balance between demand and supply, but also emphasizes the principles of justice ('adl), benefits (maslahah), equitable distribution of wealth, and the linkage between the financial sector and the real sector. Efficiency in the sharia economy is not solely measured by the achievement of economic benefits, but also by the system's ability to realize social welfare, maintain economic stability, and fulfill sharia goals (maqashid sharia). Thus, sharia economics offers a more comprehensive approach in creating economic balance and efficiency that is oriented towards sustainability and the benefit of society.